"Analysis of Financial Manager Behavior Towards Report Fraud in the AI Era" - Fitri Komariyah (Journal of Economics, Management, Accounting, Business, Educational, Technology, and Social Science, 2025)
This research aims to analyze the behavior of financial managers in facing opportunities and pressure to commit financial report fraud in the era of artificial intelligence (AI). With increasingly sophisticated technology, accounting practices and financial supervision have undergone significant transformation, but on the other hand it has also opened up new opportunities for manipulative actions. This study uses a quantitative approach through a survey of 120 financial managers in various industrial sectors in Indonesia, and is supported by in-depth interviews to enrich the data. The research results show that psychological factors such as rationalization, organizational pressure, and opportunities detected through the use of AI greatly influence the tendency for fraudulent reports to occur. In addition, technological adaptability and ethical awareness are proven to be strong moderating factors in reducing the risk of fraudulent behavior. These findings provide an important contribution to the development of internal control systems and ethics training strategies in the digital era.